BEHAVIORAL RESPONSE PATTERNS OF OCCUPANTS DURING EARTHQUAKES IN BANDA ACEH - Ulfa Mazaya; Karima Adilla; Ria Purnama; Atika Aditya (Arsitekno, 2026)
Many of the losses and casualties caused by the earthquake in Indonesia were caused by the collapse of residential buildings. Human behavior is difficult to predict during emergency situations such as an earthquake. Observation of behavior during an earthquake allows identification of safety measures to be taken during an emergency situation. These observations can provide knowledge of how behavior patterns occur when dealing with earthquake disasters. Occupant behavior can be influenced by the physical environment of the buildings. Therefore, a good building design should consider the behavior aspects. Until now, research related to behavior during earthquakes in Indonesia is still lacking. The purpose of this study is to identify what behaviors occur when facing earthquakes in residential buildings. This research was conducted with qualitative method that is exploratory. Data were collected using an open-ended online questionnaire and analyzed using the content analysis method. Sample were taken through non-random sampling to respondents who had experienced an earthquake in a residential building in Banda Aceh City. The results of the study found 7 behaviors during an earthquake with 2 groupings based on occupant movement, namely active behavior group: (1) exiting the building, (2) taking actions to protect oneself, (3) helping to evacuate others, (4) staying in the building, and (5) following other people; and passive behavior group: (1) not doing anything, (2) praying